Implementar un sistema de ventas, tele mercadeó, comisiones y seguimiento de clientes para optimizar los recursos en la empresa Omnisoft de la ciudad de quito - Alvarez Caisaguano, Adriana Vanessa (2007)
In the Company Omnisoft has been implemented a System of Sales, Telemarketing, Commissions and Control of Clients in order to optimize its resources, it provides services in a specialized way such as: to develop computer solutions completely based on the technology of Internet allowing the organizational processes automation to elevate its competitive level through its capacity and potentiality in the technology area inside the most important organizations in the country. Omnisoft was created in October first 2001; its mission is being an indispensable tool for the big companies taking advantage of its employees’ creative power.